Cardiogenic shock in patients presenting with acute left main coronary artery occlusion. (14th October 2021) - Braga, M; Calvao, J; Silva, J C; Campinas, A; Alexandre, A; Brochado, B; Silveira, J; Macedo, F
Abstract: Background and purpose: Acute myocardial infarction (AMI) due to left main coronary artery (LMCA) occlusion is a rare event, often catastrophic. Limited data are available about management and outcomes of patients with acute LMCA occlusion, including those presenting with cardiogenic shock (CS) at hospital admission. This study sought to describe patients with AMI due unprotected LMCA occlusion presenting with CS and to evaluate their in-hospital outcomes and 1-year mortality. Methods: In this retrospective 2-center study, we identified 7630 patients with ST-segment elevation myocardial infarction (STEMI) or hight risk non-ST segment elevation myocardial infarction who underwent to emergent coronary angiography between January 2008 and December 2020. Among this cohort, we analysed 94 patients who presented with unprotected LMCA occlusion (Thrombolysis In Myocardial Infarction – TIMI ≤2) and divided them in 2 groups according to presence of signs of cardiogenic shock at admission: CS and no-CS. Results: Of 94 patients with AMI due LMCA occlusion, 52 patients presented with CS (53.3%). Mean age was 62.8±11.5 years in CS and 62.0±15.9 years in no-CS patients, p=0.766. In both groups, most patients were male. STEMI presentation was more frequent in CS group (80.4% vs. 52.4%, p=0.004). Severe systolic dysfunction of left ventricle was more frequent in CS patients (81.1% vs. 33.3%, p<0.001). Compared to no-CS patients, CS group shown more often TIMI=0 (67.3% vs. 26.2%, p<0.001), collateral coronary circulation Rentrop 0–1 (95.3% vs. 75.0%, p=0.008), and slow-reflow/no-reflow phenomena (30.6% vs 3.8%, p=0.019) in emergent coronary angiography. The need of invasive mechanical ventilation (68.9% vs. 21.4%, p<0.001), and haemodialysis (20.5% vs. 2.4%, p=0.010) were more prevalent in CS patients. Likewise, mechanical circulatory support (MCS) was more frequently used in patients presented with CS (52.9% vs. 26.2%, p=0.009). In subgroup analysis, MCS implantation was not a survival predictor in CS patients (Odds ratio: 3.9 [95% confidence interval: 0.4 to 36.3], p=0.229). Ultimately, in-hospital mortality (78.8% vs. 16.7%, p<0.001) was higher in CS patients. On the other hand, in hospital survivors, there was no significant differences in 1-year mortality (11.1% vs. 23.5%, p=0.42) between both groups. Conclusions: Nearly half of patients with AMI due LMCA occlusion presented with CS signs at first medical evaluation. This subgroup of patients had higher in-hospital mortality compared to those without CS, despite MCS implantation. Whether the use of a specific MCS device or whether early use of MCS can change the outcome remains to be elucidated. CS patients who survive to index-hospitalization, had similar long-term outcomes compared to no-CS patients. Further studies are imperative in this population to refine initial medical treatment in order to improve their prognosis. FUNDunding Acknowledgement: Type of funding sources: None.